The Edler Lecture: When a Picture Is Worth 1000 Words - Shuman, Jill (MD Conference Express, 2014)
Prof Gerald Maurer presented the Edler Lecture at EuroEcho-Imaging 2014. He provided an overview of the changing imaging landscape over the past 4 decades, noting the benefits and disadvantages to using these sensitive technologies. Clinicians in Europe will soon have evidence-based guidelines to appropriately use imaging in clinical practice.